Management and outcome of middle ear adenomatous neuroendocrine tumours: A systematic review. (October 2021) - Engel, M.S.D.; van der Lans, R.J.L.; Jansen, J.C.; Leemans, C.R.; Bloemena, E.; Lissenberg-Witte, B.I.; Rijken, J.A.; Smit, C.F.; Hensen, E.F.
Highlights: Middle ear adenomatous neuroendocrine tumors (MEANTs) are rare, unpredictable tumours with a tendency to recur, sometimes after prolonged periods of time. The clinical presentation varies from a benign indolent tumor to invasive, metastatic and sometimes fatal disease. The preferred primary treatment of MEANT is complete surgical removal of the tumor. Reliable predictors for outcome are currently lacking, and prolonged follow-up is warranted. Abstract: Middle ear adenomatous neuroendocrine tumours (MEANTs) are rare, unpredictable tumours. Although most MEANTs are characterized by a benign biological behaviour and indolent growth pattern, some studies have reported locally invasive and metastastic disease. Currently, the optimal management strategy for MEANTs remains subject of debate. The aim of this study is to review the literature on MEANTs with focus on its clinical characteristics, treatment strategies and outcome. A systematic review was conducted using PubMed, Embase and Cochrane databases. A total of 111 studies comprising 198 patients with MEANT were included. Treatment modalities comprised surgery (90%), surgery with adjuvant radiotherapy (9%) and palliative (chemo)radiotherapy in (1%). Local recurrence was observed in 25% of the patients and 7% of the patients developed metastasis, over a median period of 5.7 years (range 7 months – 32 years). Twelve of 13 patients (92%) who developed metastases had a local recurrence. Four patients (2%) died of MEANT: three due to distant metastases and one due to extensive local recurrence. Reliable histopathologic predictors of outcome could not be identified. These findings indicate that the clinical presentations of MEANT vary substantially, the overall recurrence rate is considerable and initial local tumour control is paramount. Because of the unpredictable clinical course, prolonged follow-up is warranted.